2021
DOI: 10.1097/brs.0000000000004214
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Glycemic Variability as a Predictor of Adverse Outcomes Following Lumbar Fusion

Abstract: Study Design. A retrospective cross-sectional study.Objective. This study aims to evaluate the effect size of postoperative glycemic variability on surgical outcomes among patients who have undergone one-to three-level lumbar fusion. Summary of Background Data. While numerous patient characteristics have been associated with surgical outcomes after lumbar fusion, recent studies have described the measuring of postoperative glycemic variability as another promising marker. Methods. A total of 850 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Glycemic variability, as an indicator of blood glucose fluctuation, can show the stability and fluctuation range of blood glucose in a period and is an important content for evaluating whether blood glucose in diabetic patients reaches the standard. A recent study has found a certain correlation between glycemic variability and the occurrence of postoperative SSI 9 . Diabetes patients are usually accompanied by hyperglycemia.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Glycemic variability, as an indicator of blood glucose fluctuation, can show the stability and fluctuation range of blood glucose in a period and is an important content for evaluating whether blood glucose in diabetic patients reaches the standard. A recent study has found a certain correlation between glycemic variability and the occurrence of postoperative SSI 9 . Diabetes patients are usually accompanied by hyperglycemia.…”
Section: Introductionmentioning
confidence: 96%
“…A recent study has found a certain correlation between glycemic variability and the occurrence of postoperative SSI. 9 Diabetes patients are usually accompanied by hyperglycemia. Long‐term hyperglycemia can inhibit the function of inflammatory cells in the body, reduce immunity, and cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%